Analisis Keefektifan Lingkungan Pembelajaran Kimia Berbasis Web Pada Mahasiswa Pendidikan Kimia - Lisdiana, Hayyun; Suryani, Elma; Selvia Nurrohmah, Adilla; Apriliani, Layla; Saputra, Rizky (LPPM Universitas Negeri Jakarta, 2023)
This study aims to obtain information regarding the effectiveness of a web-based chemistry learning environment for students in semester 6 of the 2023/2024 academic year. Web-based learning in this study is using online learning. The research method uses a mixed method. The subjects in this study were 43 students of Chemistry Education, Jakarta State University, class of 2020. This research consists of three stages, namely the initial stage, the implementation stage, and the final stage. The data collection method used consisted of a questionnaire method with open ended questions. The questionnaire in this study used the Web Based Learning Environment Instrument (WEBLEI) with a Cronbach's alpha reliability value of 0.878. The results showed that the effectiveness of the web-based learning environment was quite good, which was indicated by the average acquisition of each scale, namely 3.65, 3.41, 3.59 and 3.44 for the access, interaction, response and outcome scales.